2018
DOI: 10.1039/c8ob01572d
|View full text |Cite
|
Sign up to set email alerts
|

Dioxane-involving reaction for the synthesis of 3-aryl-1-(2-(vinyloxy)ethoxy)isoquinolines catalyzed by AgOTf

Abstract: Dioxane was found to be involved in the reaction of 2-(arylethynyl)benzaldehydes and 3-aminopyrazine-2-carbohydrazide, and underwent a ring-opening reaction catalyzed by AgOTf. This domino type procedure provided an efficient method for the synthesis of 3-aryl-1-(2-(vinyloxy)ethoxy)isoquinolines in good yields via the loss of a molecule of 3-aminopyrazine-2-carboxamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…When 1,2-dimethoxyethane was used as the substrate, a mixture of two regioisomers 3af and 3af′ was obtained, which could be isolated by flash chromatography in 45% and 24% yields, respectively. The reason for the higher selectivity for the formation of 3af might be that the radical generated from the methylene carbon was more stable than that from the methyl carbon (see below for the reaction mechanism) . With 1,3-dioxolane and 1-methyl-2-pyrrolidinone as substrates, 3ag and 3ah were obtained as the sole product in 53% and 55% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When 1,2-dimethoxyethane was used as the substrate, a mixture of two regioisomers 3af and 3af′ was obtained, which could be isolated by flash chromatography in 45% and 24% yields, respectively. The reason for the higher selectivity for the formation of 3af might be that the radical generated from the methylene carbon was more stable than that from the methyl carbon (see below for the reaction mechanism) . With 1,3-dioxolane and 1-methyl-2-pyrrolidinone as substrates, 3ag and 3ah were obtained as the sole product in 53% and 55% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…for C–C bond formation has gained attention, not only because of the direct formation of a new C–C bond but also because these heteroatomic moieties are widely spread across the framework of many bioactive molecules . However, the application of such C–H bond functionalization in constructing structurally diverse polyheterocycles is rare . Besides, while transition-metal-catalyzed C­(sp 3 )–H functionalization reactions with noble metals were widely used, the application of inexpensive metals, such as copper or iron, remains limited and is still challenging .…”
Section: Introductionmentioning
confidence: 99%
“…[44] Pan et al reported silver-catalyzed reaction conditions for the successful conversion of 2-(arylethynyl) benzaldehydes 6 and 3-aminopyrazine-2-carbohydrazide 14 into 3-aryl-1-(2-(vinyloxy)ethoxy)isoquinolines 16 employing dioxane 15 as substrate. [45] It was quite unexpected that the dioxane undergo ring opening and take part in the reaction. To optimize the reaction conditions, different Lewis acids were screened and it was found that maximum yield was obtained when AgOTf was employed.…”
Section: Ag-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…Pan et al. reported silver‐catalyzed reaction conditions for the successful conversion of 2‐(arylethynyl)benzaldehydes 6 and 3‐aminopyrazine‐2‐carbohydrazide 14 into 3‐aryl‐1‐(2‐(vinyloxy)ethoxy)isoquinolines 16 employing dioxane 15 as substrate [45] . It was quite unexpected that the dioxane undergo ring opening and take part in the reaction.…”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%